2012
DOI: 10.1111/j.1752-0606.2011.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Class in Family Therapy Education: Experiences of Low SES Students

Abstract: In this article, we report the results of a national survey of students in COAMFTE-accredited family therapy programs who self-identify as coming from lower- or working-class backgrounds. Results of the study reveal opportunity and tension relative to family, friends, and community because of social mobility associated with graduate education. Participants describe family therapy education as middle-class centered, pointing to lack of attention to social class, marginalization, classism, and unacknowledged cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…These results are similar to those found in studies that examined experiences of other minority student groups in clinical training programs (McDowell, 2004;McDowell, Brown, Cullen, & Duyn, 2013). Individuals that identify with minority populations tend to be aware of the needs of their communities, and tend to be attuned to when their community is being left out of the conversation.…”
Section: Role As a Spokespersonsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are similar to those found in studies that examined experiences of other minority student groups in clinical training programs (McDowell, 2004;McDowell, Brown, Cullen, & Duyn, 2013). Individuals that identify with minority populations tend to be aware of the needs of their communities, and tend to be attuned to when their community is being left out of the conversation.…”
Section: Role As a Spokespersonsupporting
confidence: 81%
“…It is difficult to ascertain as to whether or not her cohort was the norm or if the other cohorts were the norm and there is currently no information made available about the number queer-identified C/MFTs or therapists in training. Other studies have highlighted the homogenous nature of the field of Couple/Marriage and Family Therapy, especially with regards to race and SES (McDowell, 2004;McDowell et al, 2013). It would be fascinating to explore how the demographic make up of clinical training programs, with regards to both the faculty and students, influences the level of satisfaction of clinical students with regard to their training as competent C/MFTs.…”
Section: Contextmentioning
confidence: 99%
“…For example, Lark and Croteau (1998) discussed the importance of mentors being a source of accurate and current information about climate and safety for their LGBT mentees. And, yet, it is simultaneously important for faculty to work to ensure acceptance and safety for a diverse student body (e.g., Edwards, Robertson, Smith, & O'Brien, 2014;McDowell, Brown, Cullen, & Duyn, 2013;McGeorge, Carlson, & Toomey, 2013;Nova, McGeorge, Carlson, 2013). In the current study, participants who self-defined as gay or lesbian reported that their mentors needed to improve their knowledge of the relevance of sexual orientation.…”
Section: Time Spent Providing Mentorshipmentioning
confidence: 99%
“…With this in mind, I am happy to see recent articles related to the treatment of the homeless (Harris‐McKoy, Woods, Brantley, & Farineau, ; Holtrop, McNeil, & McWey, ), those with physical and mental health issues (e.g., Houston‐Barrett & Wilson, ; MacPherson, Leffler, & Fristad, ; Wagner et al., ), those marginalized because of their sexual orientation, race, or other reasons (e.g., Coolhart, Baker, Farmer, Malaney, & Shipman, ; LaSala, ; Maciel & Knudson‐Martin, ; Quirk, Strokoff, Owen, France, & Bergen, ), those at risk for relational violence (Salis, Kliem, & O'Leary, ; Schneider & Brimhall, ; Taylor & Borduin, ), and substance abuse (e.g., Ladd & McCrady, ; Soloski, Kale Monk, & Durtschi, ). Similarly, we continue to publish important articles related to gender, power, culture, class, and their intersection (e.g., Knudson‐Martin et al., ; McDowell, Brown, Cullen, & Duyn, ; McDowell, Melendez‐Rhodes et al., ; Seedall, Holtrop, & Parra‐Cardona, ; Seshadri & Knudson‐Martin, ; Van Parys & Rober, ; Williams, Galick, Knudson‐Martin, & Huenergardt, ; Williams & Knudson‐Martin, ).…”
mentioning
confidence: 99%